Levofloxacin Removal from Pharmaceutical Wastewater Using Advanced Oxidation Process - Abdelnasser, Donia (AUC Knowledge Fountain, 2025)
Antibiotics are increasingly recognized as emerging pollutants in aquatic environments due to their persistence and potential to contribute to the spread of antibiotic resistance genes (ARGs) and antibiotic-resistant bacteria (ARBs). The widespread presence of these pollutants, particularly in wastewater, poses significant risks to both environmental and human health. Among these antibiotics, levofloxacin (LVX), a commonly used fluoroquinolone, has been frequently detected in wastewater streams. In addition to spreading ARG and ARBs, LVX can have toxic effects on aquatic organisms. Even at trace concentrations, it has the potential to destabilize microbial communities within aquatic ecosystems, thereby impairing ecological equilibrium. Therefore, this study investigates the removal efficiency of levofloxacin from pharmaceutical wastewater using a synthesized magnetically recoverable nanocomposite (CoFe2O4@ZnO) in photocatalytic advanced oxidation process (AOP). The conducted experimental work consisted of three phases, The first phase focused on the core-shell structured photo-catalyst synthesis and its characterization. In the second phase, the removal efficiency of LVX in a batch reactor system was studied alongside with optimizing the operating parameters including catalyst dosage, initial pH, and water turbidity at different initial LVX concentrations. Finally, the third phase tackled the feasibility of applying the obtained operating parameters in a fluidized-bed continuous flow system to investigate the removal efficiency of the LVX for seven continuous hours. The experimental results from phase 1 demonstrated that the obtained nanocomposites showed a successful formation of Cobalt Ferrite core surrounded by Zinc Oxide shell, with an average size 57 nm, and super paramagnetic properties. In phase 2, it was reported that the optimum pH for maximum LVX removal was 7 for various initial LVX concentrations ranging from 50 mg/L to 400 mg/L. It was also reported that a catalyst dosage of 1 g/l to 1.5 g/l was effective to remove LVX within 5 hours of exposing nanoparticles to UV light and that most of the removal takes place during the first 2 to 3 hours of the process. By testing high LVX concentrations, it was observed that high CNP dose and more time will be required for degradation. Moving to the impact of turbidity, by investigating 8 levels of turbidity, it was reported that the maximum allowable turbidity for the process is 140 NTU while values higher than this inhibited light penetration and hence reduced the removal efficiency. Finally, in third phase, it was concluded that the LVX followed a steady state degradation condition where it was degraded in the first 3 hours of the process with no further change in the concentration with a removal efficiency of 97%.